Attracting and Retaining English Second Language Teachers - Parks, Philippa; Riches, Caroline; Hardin, Katherine (Apprendre et enseigner aujourd’hui)

(untitled) (Conseil pédagogique interdisciplinaire du Québec, 2023)
The benefits of learning an additional language are wide-ranging. In addition to the advantage of being able to communicate in an additional language, there are cognitive and academic benefits for the learner, such as increased ability to solve problems, multitask, and enhanced first-language literacy skills compared to monolingual students. Language learning also offers benefits for society : Second-language learners demonstrate enhanced empathy, awareness of diversity, tolerance of difference, and a greater sense of social justice (O’Brien et al., 2017). Given the numerous benefits of learning an additional language, it is important to ensure the quality of second language teaching in Canada and Quebec.